Leonora's Last Act : Essays in Verdian Discourse - Parker, Roger, 1951- (Book collections on Project MUSE., 1997)
In these essays, Roger Parker brings valuable insights to bear on Verdian analysis and criticism, and does so in a way that responds both to an operagoer's love of musical drama and to a scholar's concern for recent critical trends. Parker explores works like Rigoletto, Il trovatore, La forza del destino, and Falstaff from a variety of angles, and addresses such contentious topics as the composer's involvement with Italian politics, the possibilities of an "authentic" staging of his work, and the advantages and pitfalls of analyzing his operas according to terms that his contemporaries might have understood.